Factors Affecting the Demand for People's Business Credit by Micro, Small and Medium Enterprises - Muh Yahya; Suharto Suharto; Andi Aris Mattunruang (CV. Sakura Digital Nusantara, 2023)
This study aims to determine the influence of the factors of interest rates, administration and services, environment / recommendations, and time period, on the taking of people's business credit (KUR) for micro, small and medium enterprises (MSMEs) to test the most dominant factor in taking KUR for MSMEs. The sample was 100 respondents spread across Makassar City. This type of research is quantitative research, the data source is primary data. The analysis method uses multiple regression. The results show that the variables of interest rates, administration and services, environment/recommendations, and time period simultaneously influence the taking of KUR MSMEs. The results of the t test show that interest rates, administration and services have an effect on taking KUR MSMEs, while the environment/recommendations and the time period do not have a significant effect on taking KUR MSMEs in Makassar city, the most influential factor is the interest rate factor. This is in line with the expectation that MSMEs will tend to choose lower interest rates to facilitate the fulfillment of their obligations. In addition, efficient administration and services also play an important role in the decision to take KUR for MSMEs. The speed and ease of the credit application process greatly influences MSME preferences.